Attitudes towards multilingualism and knowledge of the language of the community as an element of the educational policy in Kosovo and Metohija - Suvakovic, Aleksandra (Sociološki pregled, 2022)
The paper starts from the adopted European concept of multilingualism and lists the results of its application in Serbia‘s language policy. The results are shown of the research into the attitudes of the students in the territory of the Autonomous Province of Kosovo and Metohija towards foreign language learning, as well as learning the language of the other ethnic community. The research was conducted at the end of 2016 and the beginning of 2017 on the stratified quota sample among the students in Kosovska Mitrovica and Priština, by applying the field survey technique. According to them, it can be concluded that both populations are aware of the need to learn one (English that is dominant) or more foreign languages, the knowledge of which is relatively well self-evaluated; however, there is no developed awareness of the need to know the language of the other ethnic community, so there is a pronounced opposition to its introduction in the schooling system.
Keywords: European multilingualism policy; foreign language learning; learning the language of the other ethnic community; Serbia; Kosovo and Metohija 2016/2017